Huzurevinde kalan yaşlıların huzurevindeki yaşamlarına ilişkin algıları - Sökmen, Dilek Çevik (My University, 2008)
HUZUREVİNDE KALAN YAŞLILARIN HUZUREVİNDEKİ YAŞAMLARINA İLİŞKİN ALGILARI Bu araştırma; 60 yaşını doldurmuş ve Maltepe Huzurevinde kalmakta olan sağlıklı yaşlıların huzurevindeki yaşamlarına ilişkin algılarının incelenmesi amacıyla yapılmıştır. Örnek olay modeline uygun olarak araştırmanın evrenini Maltepe Huzurevinde kalan sağlıklı yaşlılar oluşturmaktadır. Araştırmada 60 yaşlıya ulaşılabilmiştir. Veri toplam aracı olarak anket ve görüşme yöntemi kullanılmıştır. Verilerin çözümlenmesinde frekans, yüzde analizleri ve nitel çözümleme yapılmıştır. Araştırmada elde edilen bazı önemli sonuçlar şunlardır: Araştırmaya katılan Maltepe huzurevi yaşlılarının %46,6’sını (n:28) kadın, %53,3’ünü (n:32) erkek yaşlılar oluşturmaktadır. Yaşlılarının % 11,7’sinin (n:7) okur-yazar, %35’inin (n:21) ilkokul, %11,7’sinin (n:7) ortaokul, %30’unun (n:18) lise, %5’inin (n:3) üniversite, %6,7’sinin (n:4) okur-yazar- olmadığı, %20’sinin (n:12) evli, %21,7’sinin (n:13) bekar, %58’inin (n:35) dul olduğu belirlenmiştir. Huzurevi yaşlılarından %81,7’si (n:49) kendi isteği, %8,3’ü (n:5) çocukları, %6,7’si (n:4) tanıdıkları, %3,3’ü (n:2) diğer kişiler aracılığıyla huzurevine müracaat etmişlerdir. Huzurevi yaşlılarından %6,7’si (n:4) huzurevinde kalmaktan memnun olmadığını, %3,3’ü (n:2) karasız, %90’nı (n:54) memnun olduğunu ifade etmişlerdir. Yaşlılardan huzurevinde yaşamayı başkalarına tavsiye edenler ve etmeyenler olmuştur. Tavsiye edenler güvenli bir yer olması, bakacak kimsesi olmayanların barınacağı bir yer olması, huzur bulmak isteyenlerin tercih ettiği, ekonomik açıdan avantajlı olması, her türlü hizmetin (yemek, temizlik, sağlık) hazır ayaklarına gelmesi, bahçenin güzel olması nedenleriyle tavsiye ettiklerini belirtmişlerdir. Tavsiye etmeyenler ise özgürlüklerinin sınırlanması, huzurevi konukları ile ilgili sorunlardan dolayı tavsiye etmediklerini ifade etmişlerdir. Huzurevi yaşlılarına kurum içinde bir aktivitelerinin olup olmadığı sorulmuştur.11 kişi sosyal aktivitelere katılmadığını 49 kişi de katıldığını söylemiştir. Huzurevi yaşlılarının %25’i (n:15) huzurevinde arkadaşının olmadığını, %75’i (n:45) arkadaşının olduğunu ifade etmiştir. Huzurevi yaşlılarının %11,6’sı (n:7) ziyaretçisinin gelmediğini, %88,3’ü (n:53 ) ziyaretçisinin geldiğini belirtmiştir. Ayrıca huzurevi yaşlılarından 7 kişi gönüllü kişi ve kuruluşlar tarafından ziyaret edilmediğini, 53 kişi ziyaret edildiğini belirtmiştir. Huzurevi yaşlılarının %18,3’ü (n:11) sivil toplum örgütleri ve gönüllü kişilerden beklentisinin olmadığını, %81,7’si (n:49 ) beklentisinin olduğunu söylemiştir. Huzurevi yaşlıları 4 kişi Sivil toplum örgütlerine üye olduğunu, 56 kişi üye olmadığını ifade etmiştir. Elde edilen veriler ışığında, huzurevlerinin birer yaşam alanı olup, bu yaşam alanının yaşlılar tarafından, fizyolojik, sosyal ve ekonomik, ihtiyaçlarını karşılamak üzere tercih edildiği anlaşılmaktadır. Yaşlılar huzurevine geldiği aşamada uyum sıkıntıları çekmekte olup, uyum sonrası genel bir memnuniyet oluşmaktadır. Huzurevi yaşamında oda arkadaşları, huzurevi arkadaşları ile iletişime girerek yeni bir sosyal çevre oluşturmaktadır. Ayrıca ziyaret eden sivil toplum örgütleri ve gönüllüler ile iletişim kurarak ve onların düzenlediği organizasyonlara katılarak toplumdaki kişilerle de etkileşimlerini devam ettirmektedirler. Ancak sivil toplum örgütleri ve derneklerde aktif olarak çalışmak istemediklerini kendi istedikleri organizasyonlara katılıp, yaşlılık dönemlerini daha rahat ve huzurlu geçirmek istedikleri belirlenmiştir.

THE PERCEPTIONS OF THE OLD WHO LIVE IN RESTING HOME ABOUT THEIR LIFE IN RESTING HOME This investigation has aimed at researching for the perceptions of the old who live in Maltepe Resting Home in health about the periods of their life in resting home. The old in Maltepe Resting Home has formed the environment of the research, which is arranged according to Exemplary model. We have reached 60 old people in the research. As a tool of input data sum, questionnaire and meeting face to face have been used. In the analyse of the input data, frequency, percentage analyse and qualitative analyse have been used.These are some of the results of the research: While %46,6 of the old living in Maltepe Resting Home are female, %53,3 of them are male. It has been determined that % 11,7 of the old are literate, %35 of the old have primary school degree, %11,7 of the old have secondary school degree, %30 of the old have high school degree, %5 of the old have university degree, %6,7 of the old are illiterate, %20 of the old are married, %21,7 of the old are single and %58 of the old are widow. And it has been determined that %81,7 of the old applied for the resting home willingly, %8,3 applied for the resting home with the wish of their own children, %6,7 of the old applied for the resting home with the help of their friends and %3,3 of the old applied for the resting home with others. Whereas %90 of the old have pointed out that they have been pleased to stay there, %3,3 have pointed out that they have been undecided and %6,7 have pointed out that they haven’t been pleased to stay there. Among the old, there have been old who advise living in a Resting home and the contrast. The old who recommend living in a resting Home have represented to the good sides of resting homes. They have pointed out that the home has been in secure, the home has been economic, it has a beautiful garden, it has got all of the health facilities like health care; nurse, doctor, officials, cleaning…The old who don’t recommend living in a resting home have represented to the bad sides of resting homes like restriction of their freedom and the problems among the old living in the same environment. It has been asked whether there has been any activity in the resting home or not. While 11 people have pointed out not to have joined to the activities, 49 have pointed out their participations to the activities. While %25 of the old have said that they don’t have friends, %75 of them have said that they have friends. From the old, while %11,6 of them have pointed out that they have visitors, %88,3 have pointed out that they don’t have any visitors. In addition to that, whereas 7 of the old have pointed out that they haven’t been visited by the volunteer institutions, 53 of the old have pointed out that they have been visited by the volunteer institutions. While %18,3 have pointed out that they haven’t any expectations from charities and volunteers, %81,7 of them have pointed out that they have been expectations from charities and volunteers. From the old, four people have said that they have been registered to the civil societies organizations, 56 people have pointed out that haven’t been registered to these kind of organizations. In result, it has been realized that resting homes have been preferred because of the social, economical and physiological facilities. When the old start living in resting homes, at first they have some adaptation problems. But day by day, they get used to living there. In resting homes, the old constitute a social life by living with their roommates. Besides, they have relationship with charities and volunteers and they attend to the organizations which are organized by the charities. But the old have pointed out that they don’t want to attend to these kind of organizations actively and they want to live comfortably in their old age.
Keywords: Halk Eğitimi; Yaşlılar_Psikoloji; Yaşlılık; Yaşlılık, Hizmetler